Solution for given equation -(5-(a+1)) = 9-(5-(2-3)) is a = 7
Solution:
Need to determine solution of following equation’
-(5-(a+1)) = 9-(5-(2-3))
Means need to solve the above equation for "a"
On solving operation in most internal bracket we get
-(5-(a+1)) = 9- ( 5 – ( -1))
On opening inside brackets we get,
-(5 – a – 1 ) = 9 – ( 5 +1 )
On solving remaining brackets we get
-5 + a + 1 = 9 – 6
=> a – 4 = 3
=> a = 4 + 3 = 7
=> a = 7
Hence solution for given equation -(5-(a+1)) = 9-(5-(2-3)) is a = 7